2019
DOI: 10.1016/j.bbrep.2019.100644
|View full text |Cite
|
Sign up to set email alerts
|

Development of an anti-bear podoplanin monoclonal antibody PMab-247 for immunohistochemical analysis

Abstract: Sensitive and specific monoclonal antibodies (mAbs) targeting podoplanin (PDPN) are needed for immunohistochemical analyses using formalin-fixed paraffin-embedded tissues because PDPN is known as a lymphatic endothelial cell maker in pathology. Recently, we established anti -PDPN mAbs against many species, such as human, mouse, rat, rabbit, dog, cat, bovine, pig, horse, goat, tiger, alpaca, and Tasmanian devil. However, anti-bear PDPN (bPDPN) has not been established yet. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…(20) We successfully determined the binding epitope of those mAbs. (22,34,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) These epitope mapping results showed that almost all anti-PDPN mAbs react with PLAG domains or PLDs. (7,(39)(40)(41)43,44,(49)(50)(51) The critical epitope of PMab-237 was also shown to be located in PLD (Fig.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…(20) We successfully determined the binding epitope of those mAbs. (22,34,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) These epitope mapping results showed that almost all anti-PDPN mAbs react with PLAG domains or PLDs. (7,(39)(40)(41)43,44,(49)(50)(51) The critical epitope of PMab-237 was also shown to be located in PLD (Fig.…”
Section: Discussionmentioning
confidence: 75%
“…We have demonstrated that the critical epitope of PMab-237 could include Leu82 and Thr84 of wPDPN using the deletion mutants and point mutants of wPDPN in CHO-K1 cells by flow cytometry. In our previous studies, we developed many mAbs against PDPNs of human, (24) mouse, (25) rat, (26) rabbit, (27) dog, (28) cat, (29) bovine, (30) horse, (31) Tasmanian devil, (32) alpaca, (33) bear, (34) tiger, (35) goat, (36) pig, (37,38) and whale. (20) We successfully determined the binding epitope of those mAbs.…”
Section: Discussionmentioning
confidence: 99%
“…(11) In this study, we selected a novel anti-bPDPN mAb (PMab-241) of IgG 2b subclass from previously established anti-bPDPN mAbs. (10) PMab-241 reacted with CHO/bPDPN, not parental CHO-K1 cells in flow cytometry (Fig. 1).…”
Section: Resultsmentioning
confidence: 93%
“…Although we have already established an anti-bPDPN mAb (PMab-247), which is sensitive and specific for immunohistochemical analyses, (10) it is difficult to distinguish lymphatic endothelial cells from type I alveolar cells in the bear lung using PMab-247. (11) In this study, we selected a novel anti-bPDPN mAb (PMab-241) of IgG 2b subclass from previously established anti-bPDPN mAbs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation